2002
DOI: 10.1086/340039
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Lifetimes of Eu i , ii , and iii and Transition Probabilities of Eu i

Abstract: Radiative lifetimes of 12 odd-parity and 73 even-parity levels of Eu i, 26 even-parity levels of Eu ii, and three even-parity levels of Eu iii have been measured with time-resolved laser-induced fluorescence. These lifetimes are accurate to AE5%. In addition, Eu i branching fractions have been measured with Fourier-transform spectrometry. These are combined with the radiative lifetimes to yield absolute transition probabilities for 140 transitions of Eu i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 42 publications
3
38
0
Order By: Relevance
“…The chosen scaling factors are 0.55 for the 4f-5d transitions and 0.86 for the 6s-6p and 5d-6p transitions. The first scaling factor agrees with the Eu iii experimental lifetimes measured by Zhang et al (2000) and Den Hartog et al (2002) (same as , while the second one fits measured values of the lifetimes for the 5d-6p transitions in the second spectra of several lanthanides, for example, in Nd iii (Zhang et al 2002a; calculations by Ryabchikova et al 2006) and in Dy iii (Zhang et al 2002b; calculations by the present authors).…”
Section: But This Technique Does Not Work For Transitions 4fsupporting
confidence: 90%
See 2 more Smart Citations
“…The chosen scaling factors are 0.55 for the 4f-5d transitions and 0.86 for the 6s-6p and 5d-6p transitions. The first scaling factor agrees with the Eu iii experimental lifetimes measured by Zhang et al (2000) and Den Hartog et al (2002) (same as , while the second one fits measured values of the lifetimes for the 5d-6p transitions in the second spectra of several lanthanides, for example, in Nd iii (Zhang et al 2002a; calculations by Ryabchikova et al 2006) and in Dy iii (Zhang et al 2002b; calculations by the present authors).…”
Section: But This Technique Does Not Work For Transitions 4fsupporting
confidence: 90%
“…In addition to the approach by Mashonkina et al (2002), the core polarisation effects were included in the calculations leading to a modification of ab initio transition integrals. As a result, about 10% deviation of calculated lifetimes for the 5d 8 P term levels from the most accurate measurements (Den Hartog et al 2002) was achieved. Calculated by , oscillator strengths for about 900 lines can be found in the dream data base created at Mons University (Biémont et al 1999).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They include electronic bandwidth limitations, cascade fluorescence, Zeeman quantum beats, and atomic motion time-of-flight effects, among others. These systematic effects are discussed in detail elsewhere (see, e.g., Den Hartog et al 1999Hartog et al , 2002 and will not be discussed further here. As a means of verifying that the measurements are within the stated uncertainties, we perform periodic end-to-end tests of the experiment by measuring a set of well-known lifetimes.…”
Section: Radiative Lifetime Measurementsmentioning
confidence: 99%
“…The NIST Atomic Spectra Database references work from 1975, but more recent gas phase lifetime measurements of this and other P states of atomic Eu are now available. The most recent study 15 identified a lifetime of 870 ± 44 ns for the z 6 P 7/2 ↔ a 8 S 7/2 transition using laser induced fluorescence. Clearly there is a discrepancy between the solid state and the gas phase lifetimes recorded.…”
Section: Z 6 P State Lifetimementioning
confidence: 99%